(a) Rationalise the denominator and leave the answer in simplest surd form: \( \begin{array}{llll}\text { (1) } \frac{3}{\sqrt{6}} & \text { (2) } \frac{2}{5 \sqrt{2}} & \text { (3) } \frac{3}{\sqrt[3]{9}} & \text { (4) } \frac{2}{4+\sqrt{2}}\end{array} \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To rationalise the denominators of the given fractions, follow these steps: (1) For \( \frac{3}{\sqrt{6}} \): Multiply the numerator and denominator by \( \sqrt{6} \). \[ \frac{3}{\sqrt{6}} \times \frac{\sqrt{6}}{\sqrt{6}} = \frac{3\sqrt{6}}{6} = \frac{\sqrt{6}}{2} \] (2) For \( \frac{2}{5\sqrt{2}} \): Multiply the numerator and denominator by \( \sqrt{2} \). \[ \frac{2}{5\sqrt{2}} \times \frac{\sqrt{2}}{\sqrt{2}} = \frac{2\sqrt{2}}{10} = \frac{\sqrt{2}}{5} \] (3) For \( \frac{3}{\sqrt[3]{9}} \): Write \( \sqrt[3]{9} = 9^{1/3} = (3^2)^{1/3} = 3^{2/3} \). To rationalise, multiply by \( \frac{3^{1/3}}{3^{1/3}} \): \[ \frac{3}{3^{2/3}} \times \frac{3^{1/3}}{3^{1/3}} = \frac{3^{1/3}}{3^{1/3}} = 3^{1/3} \] (4) For \( \frac{2}{4+\sqrt{2}} \): Multiply by the conjugate \( 4 - \sqrt{2} \). \[ \frac{2(4 - \sqrt{2})}{(4 + \sqrt{2})(4 - \sqrt{2})} = \frac{8 - 2\sqrt{2}}{16 - 2} = \frac{8 - 2\sqrt{2}}{14} = \frac{4 - \sqrt{2}}{7} \] Final answers in simplest surd form: (1) \( \frac{\sqrt{6}}{2} \) (2) \( \frac{\sqrt{2}}{5} \) (3) \( 3^{1/3} \) (4) \( \frac{4 - \sqrt{2}}{7} \)